The nanotechnology challenge : creating legal institutions for uncertain risks - Dana, David, 1963- (Cambridge University Press, 2012)
"This book is about nanotechnology, very tiny substances that are manipulated to act in all sorts of extraordinary ways, and that many think have or are about to usher in the next industrial revolution. The focus of the book is how society can continue to reap economic and other benefits from nanotechnology, while addressing the possible risk to human and the environment from nanotechnology. Leading scholars offer a range of solutions to the challenge of regulating nanotechnology in a way that allows for continued fast innovation worldwide while making certain we limit or avoid the possible harms from nanotechnology"--Resumé vydavatele
Brožované vydání vyšlo v roce 2014
Keywords: nanotechnologie -- právní aspekty; nanotechnologie -- environmentální aspekty; nanotechnologie -- ekonomické aspekty; nanotechnology -- legal aspects; nanotechnology -- environmental aspects; nanotechnology -- economic aspects; sborníky; papers of several authors